O lugar do estudo das mídias na formação de professores numa perspectiva emancipatória - Silva, Márcia Barbosa da (2011)
The media currently play a dual role in the physical and symbolic structure of social organization. It is through the media that companies have achieved control of their distribution and production. It is not only through the media, but mainly so, that certain world views circulate and are legitimized. Access to material and symbolic goods has become a mark of social distinction. The project of a more democratic society also involves the preparation of its citizens to be able both to deal with the media products that already circulate as well as to develop a critical perspective of media products. This research stemmed from the need to understand what place this study of the media occupies in training for teachers in early grades, given that children are already immersed in a media world from an early age. This research shows that this is a place which is under construction and despite the existing adverse conditions, emancipatory practices are being developed. The research is guided by the study of the media in teacher education from an emancipatory perspective. This perspective develops in a time that, in this case, has proved slow and fragmented, but not nonexistent. The process of teacher training is influenced by working conditions and educational policies that hinder both working with the media in school and also improving the critical understanding of the media. The research shows that training opportunities, even in these conditions, can allow for more meaningful criticism. The emancipatory perspective also includes a reflection on practices. These practices are being developed and this research sought to provide support for a proposed study of the media from this perspective